2012
DOI: 10.1002/bab.1042
|View full text |Cite
|
Sign up to set email alerts
|

Addressing endotoxin issues in bioengineered heparin

Abstract: Heparin is a widely used clinical anticoagulant that is prepared from pig intestine. A contamination of heparin in 2008 has led to a reexamination of animal-derived pharmaceuticals. A bioengineered heparin prepared by bacterial fermentation and chemical and enzymatic processing is currently under development. This study examines the challenges of reducing or removing endotoxins associated with this process that are necessary to proceed with preclinical in vivo evaluation of bioengineered heparin. The current p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A significant reduction in endotoxin levels (2.5 log) was recorded for chitosan‐purified heparosan while SAX purified heparosan still contained a high endotoxin load. This endotoxin reduction is important, as use of chitosan in the bioengineered heparin process can circumvent the need for a change in enzyme expression systems to mitigate endotoxin risk arising due to use of E. coli based expression systems . Further characterization of this process, however, is necessary to ascertain selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in endotoxin levels (2.5 log) was recorded for chitosan‐purified heparosan while SAX purified heparosan still contained a high endotoxin load. This endotoxin reduction is important, as use of chitosan in the bioengineered heparin process can circumvent the need for a change in enzyme expression systems to mitigate endotoxin risk arising due to use of E. coli based expression systems . Further characterization of this process, however, is necessary to ascertain selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…This endotoxin reduction is important, as use of chitosan in the bioengineered heparin process can circumvent the need for a change in enzyme expression systems to mitigate endotoxin risk arising due to use of E. coli based expression systems. [49][50][51][52] Further characterization of this process, however, is necessary to ascertain selectivity. The purified products, appearing as a single peak, suggest a higher molecular weight of heparosan compared to ammonium sulfate purified heparosan derived from the same fermentation broth.…”
Section: Characterization Of Heparosan Products Purified Using Sax Chmentioning
confidence: 99%
“…DEAE-Sephadex chromatography is a method reported to efficiently remove LPS from proteins (Hou et al 1990). Suwan et al (Suwan et al 2012) have reported that anion-exchange chromatography was efficient to remove endotoxins from heparosan (a non-sulfated precursor of heparin), but not from sulfated heparin. The inefficiency was attributed to the binding of heparin to DEAE due to the low pKa value of the sulfate groups.…”
Section: Discussionmentioning
confidence: 99%